Exploring the Prospective Teachers’ Critical Thinking and Critical Analysis Skills (Jurnal Pendidikan IPA Indonesia, 2019)
This study aimed to explore the prospective teachers’ critical thinking and critical analysis skills based on gender. This is a descriptive quantitative study with survey methods. The research samples were 50 males and 50 females who take the anatomy and plant development courses selected using purposive random sampling. The data of prospective teachers’ critical thinking and critical analysis skills were collected using the instrument developed that was validated by two experts and tested on 20 biology education students. The data of prospective teachers’ critical thinking and critical analysis skills were analyzed descriptively and statistically using a software (IBM SPSS Statistic 23). The results of the study show that (1) the prospective teachers’ critical thinking and critical analysis skills as underdeveloped; (2) critical thinking skills differ in the components of interpretation, explanation, and self-regulation; (3) critical analysis skills differ on the explanation and interpretations; and (4) there is a positive correlation between prospective teachers’ critical thinking and critical analysis skills. Based on the result of the study, serious and planned handling can be done through important learning. The results of this study can be an initial reference and priority determination of lecturers in teaching prospective teachers’ critical thinking and critical analysis skills based on gender.